2004
DOI: 10.1186/1468-6708-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence and noninferiority trials – are they viable alternatives for registration of new drugs? (III)

Abstract: The scientific community's reliance on active-controlled trials is steadily increasing, as widespread agreement emerges concerning the role of these trials as viable alternatives to placebo trials. These trials present substantial challenges with regard to design and interpretation as their complexity increases, and the potential need for larger sample sizes impacts the cost and time variables of the drug development process. The potential efficacy and safety benefits derived from these trials may never be dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 59 publications
2
31
0
2
Order By: Relevance
“…Placebo-controlled trials are still used to demonstrate effectiveness of new drugs and, for circumstance in which no increased risk for patients is foreseen, use of placebo seems appropriate and ethical, provided that the patients are fully informed and that they give written, informed consent [34-36]. …”
Section: Study Design – Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placebo-controlled trials are still used to demonstrate effectiveness of new drugs and, for circumstance in which no increased risk for patients is foreseen, use of placebo seems appropriate and ethical, provided that the patients are fully informed and that they give written, informed consent [34-36]. …”
Section: Study Design – Methodological Considerationsmentioning
confidence: 99%
“…[34]. Commonly, the primary objective of an equivalence/noninferiority trial is to demonstrate that the efficacy of a new treatment matches that of the control treatment while, in the "thorough QT/QTc study", the goal is to demonstrate that the safety of the new drug is equal or at least not worse than that of the control agent.…”
Section: Study Design – Methodological Considerationsmentioning
confidence: 99%
“…The alternative hypothesis above implies that at least I − k trials have shown the noninferiority, to which we refer as "consistency of noninferiority." This hypothesis setting has been used by many authors (see e.g., Antman, 2001;Garcia, 2005;Pater, 2004) in practical noninferiority trials. The integer k is a threshold representing the number of "inferior" trials that could be tolerated among I trials, while the consistency of noninferiority among all trials is still confirmed.…”
Section: The Testing Procedures Based On Multiple Meansmentioning
confidence: 99%
“…Trial sensitivity is the capability of determining an effective placebo treatment or, on the whole, of detecting differences between treatments when they actually exist 12 . It depends on factors such as the magnitude of the treatment effect and the quality of study conduction, besides adherence, patient selection criteria and excess of data variability.…”
Section: Trial Sensitivitymentioning
confidence: 99%